Electromyography variables during the golf swing: A literature review - Marta, S.; Silva, L.; Castro, M. A.; Pezarat-Correia, P.; Cabri, J. (Journal of Electromyography and Kinesiology, 2012)
The aim of the study was to review systematically the literature available on electromyographic (EMG) variables of the golf swing. From the 19 studies found, a high variety of EMG methodologies were reported. With respect to EMG intensity, the right erector spinae seems to be highly activated, especially during the acceleration phase, whereas the oblique abdominal muscles showed moderate to low levels of activation. The pectoralis major, subscapularis and latissimus dorsi muscles of both sides showed their peak activity during the acceleration phase. High muscle activity was found in the forearm muscles, especially in the wrist flexor muscles demonstrating activity levels above the maximal voluntary contraction. In the lower limb higher muscle activity of the trail side was found. There is no consensus on the influence of the golf club used on the neuromuscular patterns described. Furthermore, there is a lack of studies on average golf players, since most studies were executed on professional or low handicap golfers.